Noun Phrases as expressions of evidentiality: an analysis of four English abstract nouns and their Spanish equivalents - Carretero, Marta (Kalbotyra, 2017)
This paper presents an analysis of the expression of evidentiality with the English nouns evidence, indication, proof and sign and their Spanish equivalents evidencia, indicación, prueba and señal. The nouns are described as shell nouns having the properties of encapsulating, signalling and labelling. The delimitation of their evidential and non-evidential uses is determined by three factors: existence of a qualified proposition (Belief), non-occurrence within an irrealis context and constant value of the evidential qualification when the Belief refers to a plurality of events. The difficulties posed by the delimitation illustrate the problems involved in determining the scope of evidentiality when expressed by lexical devices belonging to the content of a proposition. A quantitative analysis was carried out on 400 occurrences of the nouns, extracted from two comparable corpora. The results reveal that all the nouns except two expressed evidentiality in most cases, that the linguistic context in which they appear shows great variation in terms of syntax and information structure, and that the labelling function is prominent. The results also uncover idiosyncratic evidential expressions with some of the nouns.